Screening of Germinated Rice Variety with High γ-aminobutyric Acid Content - WU Qi-fei; ZHANG Zi-yang; MI Xing-qiong; LIU Shu-yi; XU Bin (Liang you shipin ke-ji)
To scientifically and systematically screen rice varieties with high γ-aminobutyric acid (GABA) content, 16 rice varieties from various regions of China were subjected to heating and humidifying treatment to enhance γ-aminobutyric acid (GABA) content. By determining parameters including glutamic acid (Glu) content , glutamic acid decarboxylase (GAD) activity, germination rate and water absorption rate, rice varieties suitable for GABA enrichment were screened. The results showed that significant regional and varietal differences in GABA enrichment efficiency using the heating and humidification method on rice grains. And the GABA content of japonica rice was higher than that of indica rice both before and after enrichment with Jiangsu japonica rice exhibiting the highest GABA increment. The GABA content and increment of Nanjing 3908 and Nanjing 46 after enrichment were both at relatively high levels.The GAD activity after enrichment can be used as an indicator for screening rice varieties with high GABA. Germination rate and water absorption rate (<8 h) can be used as auxiliary predictors of GABA enrichment in rice grains. In conclusion, using GAD activity as a reference index, combined with parameters such as germination rate and water absorption rate of rice grains，allows for the effective screening of rice varieties suitable for GABA enrichment.